ANALYSIS OF REGULARITIES IN DISTRIBUTION OF EARTHQUAKES BY FOCAL DISPLACEMENT IN THE KURIL-OKHOTSK REGION BEFORE THE CATASTROPHIC SIMUSHIR EARTHQUAKE OF 15 NOVEMBER 2006 - Timofei K. Zlobin; Anastasia Yu. Polets (Геодинамика и тектонофизика, 2015)
The catastrophic Simushir earthquake occurred on 15 November 2006 in the Kuril-Okhotsk region in the Middle Kuril Islands which is a transition zone between the Eurasian continent and the Pacific Ocean. It was followed by numerous strong earthquakes. It is established that the catastrophic earthquake was prepared on a site characterized by increased relative effective pressures which is located at the border of the low-pressure area (Figure 1).Based on data from GlobalCMT (Harvard), earthquake focal mechanisms were reconstructed, and tectonic stresses, the seismotectonic setting and the earthquakes distribution pattern were studied for analysis of the field of stresses in the region before to the Simushir earthquake (Figures 2 and 3; Table 1).Five areas of various types of movement were determined. Three of them are stretched along the Kuril Islands. It is established that seismodislocations in earthquake focal areas are regularly distributed. In each of the determined areas, displacements of a specific type (shear or reverse shear) are concentrated and give evidence of the alteration and change of zones characterized by horizontal stretching and compression.The presence of the horizontal stretching and compression zones can be explained by a model of subduction (Figure 4). Detailed studies of the state of stresses of the Kuril region confirm such zones (Figure 5). Recent GeodynamicsThe established specific features of tectonic stresses before the catastrophic Simushir earthquake of 15 November 2006 contribute to studies of earthquake forecasting problems. The state of stresses and the geodynamic conditions suggesting occurrence of new earthquakes can be assessed from the data on the distribution of horizontal compression, stretching and shear areas of the Earth’s crust and the upper mantle in the Kuril region.